2008
DOI: 10.1021/la703106s
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wettability of Molecularly Thin Liquid Films by Nanostructures

Abstract: The patterning of liquid thin films on solid surfaces is very important in various fields of science and engineering related to surfaces and interfaces. A method of nanometer-scale patterning of a molecularly thin liquid film on a silicon substrate using the lyophobicity of the oxide nanostructures has recently been reported (Fukuzawa, K.; Deguchi, T.; Kawamura, J.; Mitsuya, Y.; Muramatsu, T.; Zhang, H. Appl. Phys. Lett. 2005, 87, 203108). However, the origin of the lyophobicity of the nanostructure with a hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Comparing published works that study liquid spreading on substrates with unidirectional nanoscale grooves, we find that similar observations are documented for different substrates, groove shapes, and liquids, using both simulations and experiments. However, some researchers explain that liquid spreading is accelerated along a groove [10,12], whereas others describe an energy barrier that seemingly confines spreading perpendicular to the groove direction [11,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing published works that study liquid spreading on substrates with unidirectional nanoscale grooves, we find that similar observations are documented for different substrates, groove shapes, and liquids, using both simulations and experiments. However, some researchers explain that liquid spreading is accelerated along a groove [10,12], whereas others describe an energy barrier that seemingly confines spreading perpendicular to the groove direction [11,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to create anisotropic spreading in particular, which enables liquid spreading to occur in a user-specified direction, finds application in micro/nanofluidics, 7 flexible electronics, 8 and drag reduction surfaces. 7 Several research groups have shown both experimentally and numerically that unidirectionally textured substrates lead to anisotropic spreading, where liquids spread preferentially in the direction parallel to the texture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ability to create anisotropic spreading in particular, which enables liquid spreading to occur in a user-specified direction, finds application in micro/nanofluidics, flexible electronics, and drag reduction surfaces . Several research groups have shown both experimentally and numerically that unidirectionally textured substrates lead to anisotropic spreading, where liquids spread preferentially in the direction parallel to the texture. Anisotropic spreading on unidirectionally textured substrates is most commonly explained by texture peaks, which impose a mechanical barrier that effectively “pins” the three-phase (solid/liquid/gas) contact line of the spreading liquid, inhibiting spreading in the direction perpendicular to the texture. , The texture peaks are often described as energetic barriers that oppose wetting, which Yong and Zhang attribute to a high local atomic density at texture peaks, based on the results of molecular dynamics (MD) simulations (texture height of 1.85-23.77 Å).…”
Section: Introductionmentioning
confidence: 99%
“…Checco and co-workers , measured the meniscus shape of thin organic liquid films (∼5 nm thick ethanol and octane films) on a nonwettable surface with wettable nanostripes using amplitude modulation atomic force microscopy (AM-AFM) in the noncontact regime. Fukuzawa et al measured the meniscus shape of a perfluoropolyether lubricant film with a thickness of a few nanometers on a silicon surface with oxide nanostructures using AFM. Seemann et al used AFM to measure the wetting morphologies of polystyrene on silicon microstructures.…”
Section: Introductionmentioning
confidence: 99%